2014
DOI: 10.1186/s12968-014-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric cardiovascular magnetic resonance surveillance of acute cardiac allograft rejection and characterisation of transplantation-associated myocardial injury: a pilot study

Abstract: BackgroundSerial surveillance endomyocardial biopsies are performed in patients who have recently undergone heart transplantation in order to detect acute cardiac allograft rejection (ACAR) before symptoms occur, however the biopsy process is associated with a number of limitations. This study aimed to prospectively and longitudinally evaluate the performance of multiparametric cardiovascular magnetic resonance (CMR) for detecting and monitoring ACAR in the early phase post-transplant, and characterize graft r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 26 publications
6
43
4
1
Order By: Relevance
“…Also, importantly, both studies included patients beyond 1 year post-transplant, thus reducing the effect of transplant-related myocardial injury, described above, on T 2 measurements, but also missing the window in which early detection of ACAR is thought to be most useful. In a recent study in which 22 patients were each scanned on four occasions over the first 6 months posttransplant (unselected on the basis of rejection), there was no significant difference in T 2 values between significant and non-significant rejection [5]. In part, this may reflect the small numbers of rejection episodes, but also, as described above, raised T 2 (and T 1 ) values were commonly observed in the early period post-transplant irrespective of rejection status, thus limiting the ability of CMR T 2 to detect rejection.…”
Section: Acute Rejectionmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, importantly, both studies included patients beyond 1 year post-transplant, thus reducing the effect of transplant-related myocardial injury, described above, on T 2 measurements, but also missing the window in which early detection of ACAR is thought to be most useful. In a recent study in which 22 patients were each scanned on four occasions over the first 6 months posttransplant (unselected on the basis of rejection), there was no significant difference in T 2 values between significant and non-significant rejection [5]. In part, this may reflect the small numbers of rejection episodes, but also, as described above, raised T 2 (and T 1 ) values were commonly observed in the early period post-transplant irrespective of rejection status, thus limiting the ability of CMR T 2 to detect rejection.…”
Section: Acute Rejectionmentioning
confidence: 83%
“…Nevertheless, ejection fraction is usually preserved in the newly transplanted heart. Abnormalities in myocardial strain and long axis function however are detectable and work performed using multiparametric CMR has demonstrated evidence of myocardial oedema during the first 5 months post-transplant, independent of rejection, with globally elevated myocardial T 1 and T 2 relaxation times [5]. Myocardial perfusion reserve, indicative of microvascular dysfunction, also appears to be impaired during this period.…”
Section: Typical Cmr Appearancesmentioning
confidence: 96%
“…Acute rejection is characterized histologically by inflammation of the myocardium while chronic or repeated episodes of rejection have been associated with fibrotic remodeling[7,23,24]. Native T1 and ECV have been explored as markers of ACR in a pilot study in adults after HT but an association with rejection has yet to be demonstrated[8]. In the current study, albeit in a limited number of patients, ECV and native T1 times did not distinguish between < 2R and ≥ 2R ISHLT rejection.…”
Section: Discussionmentioning
confidence: 99%
“…However, CMR measurements used in adults for the detection of rejection or myocardial inflammation, including T2-weighted imaging[5,6], native T1 times and extracellular volume fractions (ECVs) derived from T1 mapping[7], myocardial thickness, ventricular volumes and ejection fraction (EF)[8,9] have not been systematically evaluated in pediatric HT recipients with EMB-proven ACR.…”
Section: Introductionmentioning
confidence: 99%
“…The use of techniques to characterise components of myocardial injury, [113] myocardial edema, myocardium at risk, myocardial hemorrhage, [114] microvascular obstruction [115] and hibernation, [116] has also grown.…”
Section: Myocardial Infarctionmentioning
confidence: 99%